Trands towards Travel and Its Relationship to Social Harmony A Field Study on A sample of Graduate Student at The University of Damascus (Journal of Hama University, 2020)
The aim of this research is to identify the trends towards traveling and its relation to social harmony, from the point of view of a sample of postgraduate students at Damascus University. To achieve the research objective, the researcher prepared the research tools consisting of a scale of migration trend consisting of 25 items, the scale of social harmony and consisted of 41 items. The tools were distributed to a sample of 82 graduate students at Damascus University. The results of the study showed a high degree of approval and a positive trend toward traveling among postgraduate students in the Faculty of Education, University of Damascus. The results of the study also showed a strong adverse correlation between a sample of post-graduate students at Damascus University, as well as statistically significant differences between the average scores of the sample of the research sample on the trend of traveling according to gender variable, and the absence of statistically significant differences between the average scores of individuals in the research sample on the scale of trends towards traveling according to the social status variable (single, married), the state of work (working, not working).